ALPINE SKIING AS LEISURE ACTIVITY PRACTICED AFTER A SPECIFIC TRAINING - Camelia Daniela PLĂSTOI (Editura Universitatii Transilvania din Brasov, 2018)
In the current society, the use of specific training in alpine skiing is facilitated by the presence of the rental centers, for the necessary sports equipment and by the presence of ski instructors. The learning of alpine skiing as a leisure activity after a specific training is followed by a decrease in the number of injuries, correct assimilation of the basic notions of skiing on the slopes, gaining self‐confidence, etc. Learning and then practicing alpine skiing involves assimilation of information in a certain way, thus appealing to the experience of the communicator and the way the beneficiary is approached, which will allow a correct, rapid assimilation, with positive long‐term valences and new practical and theoretical notions.